Impact of Oil-Based Mud Filtrate on Phase Behavior and PVT Properties of Gas Condensate Reservoir Fluids (Journal of Earth Energy Science, Engineering, and Technology, 2026)
The impact of oil-based-mud (OBM) carryover on gas-condensate PVT behavior by comparing duplicate constant-composition expansion (CCE) tests and single-phase properties from an “original” (uncontaminated) run and a “contaminated” run was investigated. Compositional evidence indicates heavy-end enrichment (C13+) in the contaminated sample, which manifests above the dewpoint as slightly lower gas deviation factors (Δz ≈ 0.01–0.03) and higher gas viscosities (+5–8%), while (Bg) and (cg) remain within typical laboratory scatter. Both datasets place the dewpoint near ~2800–2900 psig. The principal divergence occurs in the CCE liquid-dropout response: the uncontaminated run exhibits a physically consistent retrograde curve with a credible maximum of ~0.30–0.35 at ~700–900 psig followed by decline at lower pressures, whereas the contaminated run yields systematically elevated liquid fractions with an exaggerated peak of ~0.60–0.65 and persistent low-pressure excess, patterns indicative of contamination and/or handling artefacts. Relative-volume trends overlap closely between runs, confirming a reproducible bulk P–V response. In subsequent work, we will calibrate the Equation of State (EOS) using only the uncontaminated dataset, adopting a dewpoint of ~2800–2900 psig and fitting to the uncontaminated z(P), μg(P), Bg(P), cg(P), and CCE dropout curve, while reserving the contaminated series for targeted sensitivity analyses. Practically, these findings underscore the need for rigorous sampling/decontamination protocols and cross-validation of composition against CCE trends to avoid overestimating condensate yield and near-wellbore liquid banking.